Improving the quality of maternal and newborn health outcomes through a clinical mentorship program in the Democratic Republic of the Congo: study protocol - Xu Xiong; Rebecca Carter; Paul-Samson L; Elvis C. Kuburhanwa; Francine Kimanuka; Freddy Salumu; Guy Clarysse; Baudouin Kalume Tutu; Sylvain Yuma; Alain Mboko Iyeti; Julie H. Hernandez; Jeffrey G. Shaffer; et al. (BMC, 2019)
Abstract Background The Democratic Republic of the Congo (DRC) boasts one of the highest rates of institutional deliveries in sub-Saharan Africa (80%), with eight out of every ten births also assisted by a skilled provider. However, the maternal and neonatal mortality are still among the highest in the world, which demonstrates the poor in-facility quality of maternal and newborn care. The objective of this ongoing project is to design, implement, and evaluate a clinical mentorship program in 72 health facilities in two rural provinces of Kwango and Kwilu, DRC. Methods This is an ongoing quasi-experimental study. In the 72 facilities, 48 facilities were assigned to the group where the clinical mentorship program is being implemented (intervention group), and 24 facilities were assigned to the group where the clinical mentorship program is not being implemented (control group). The groups were selected and assigned based on administrative criteria, taking into account the number of deliveries in each facility, the coverage of health zones, accessibility, and ease of implementation of a clinical mentorship program. The main activities are organizing and training a national team of mentors (including senior midwives, obstetricians, and pediatricians) in clinical mentoring, deploying them to mentor all health providers (mentees) performing maternal and newborn health (MNH) services, and providing in-service training in routine and Emergency Obstetrical and Newborn Care (EmONC) to the mentees in health facilities over an 18-month period. Baseline and endline assessments are carried out to evaluate the effectiveness of the clinical mentorship program on the quality of MNH care and the effective coverage of key interventions to reduce maternal and neonatal mortality. Findings will be disseminated nationwide and internationally, as scientific evidence is scarce. A national strategy, guidelines, and tools for clinical mentorship in MNH will be developed for replication in other provinces, thus benefitting the entire country. Discussion This is the largest project on clinical mentorship aimed to improving the quality of MNH care in Africa. This program is expected to generate one of the first pieces of scientific evidence on the effectiveness of a clinical mentorship program in MNH on a scientifically designed and sustainable model.